Development of a porcine model of skin and soft-tissue infection caused by Staphylococcus aureus, including methicillin-resistant strains suitable for testing topical antimicrobial agents - Raška, Filip; Lipový, Břetislav; Kobzová, Šárka; Vacek, Lukáš; Jarošová, Rea; Kleknerová, Dominika; Matiašková, Katarína; Makovický, Peter; Vícenová, Monika; Jeklová, Edita; Pantůček, Roman; Faldyna, Martin; et al. (Animal models and experimental medicine, 2025)
BACKGROUND: In view of the ever-increasing representation of Staphylococcus spp. strains resistant to various antibiotics, the development of in vivo models for evaluation of novel antimicrobials is of utmost importance. METHODS: In this article, we describe the development of a fully immunocompetent porcine model of extensive skin and soft tissue damage suitable for testing topical antimicrobial agents that matches the real clinical situation. The model was developed in three consecutive stages with protocols for each stage amended based on the results of the previous one. RESULTS: In the final model, 10 excisions of the skin and underlying soft tissue were created in each pig under general anesthesia, with additional incisions to the fascia performed at the base of the defects and immediately inoculated with Staphylococcus aureus suspension. One pig was not inoculated and used as the negative control. Subsequently, the bandages were changed on Days 4, 8, 11, and 15. At these time points, a filter paper imprint technique (FPIT) was made from each wound for semi-quantitative microbiological evaluation. Tissue samples from the base of the wound together with the adjacent intact tissue of three randomly selected defects of each pig were taken for microbiological, histopathological, and molecular-biological examination. The infection with the inoculated S. aureus strains was sufficient during the whole experiment as confirmed by both FPIT and from tissue samples. The dynamics of the inflammatory markers and clinical signs of infection are also described. CONCLUSIONS: A successfully developed porcine model is suitable for in vivo testing of novel short-acting topical antimicrobial agents.
Keywords: Animals; skin and soft‐tissue infection (SSTI); stafylokokové infekce kůže; animal model; Staphylococcal Skin Infections; Soft Tissue Infections; Anti-Bacterial Agents; prasata; kůže; methicilin rezistentní Staphylococcus aureus; antimicrobial agents; Staphylococcus aureus; stafylokokové infekce; Administration, Topical; modely nemocí na zvířatech; aplikace lokální; Swine; Skin; Disease Models, Animal; infekce měkkých tkání; Staphylococcal Infections; wound infection; zvířata; porcine model; antibakteriální látky; Methicillin-Resistant Staphylococcus aureus